2021
DOI: 10.1016/j.ophtha.2021.04.032
|View full text |Cite
|
Sign up to set email alerts
|

The Risks and Benefits of Myopia Control

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
139
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 160 publications
0
139
0
1
Order By: Relevance
“…The 21 st century has seen our perception of myopia transition from a benign refractive condition to a disease that represents an important public health issue. The American Academy of Ophthalmology's Board of Trustees, for example, believes that “myopia is a high‐priority cause of visual impairment, warranting a timely evaluation and synthesis of the scientific literature and formulation of an action plan to address the issue from different perspectives.” 1 Increasing levels of myopia are strongly associated with an increased risk of a number of eye diseases including myopic maculopathy, open angle glaucoma, posterior subcapsular cataract and retinal detachment 2–4 . Likewise, each additional dioptre of myopia is associated with a 30% increased risk of visual impairment 4 …”
Section: Introductionmentioning
confidence: 99%
“…The 21 st century has seen our perception of myopia transition from a benign refractive condition to a disease that represents an important public health issue. The American Academy of Ophthalmology's Board of Trustees, for example, believes that “myopia is a high‐priority cause of visual impairment, warranting a timely evaluation and synthesis of the scientific literature and formulation of an action plan to address the issue from different perspectives.” 1 Increasing levels of myopia are strongly associated with an increased risk of a number of eye diseases including myopic maculopathy, open angle glaucoma, posterior subcapsular cataract and retinal detachment 2–4 . Likewise, each additional dioptre of myopia is associated with a 30% increased risk of visual impairment 4 …”
Section: Introductionmentioning
confidence: 99%
“…With children being the primary demographic for orthokeratology, it is reassuring to see that, similar to large-scale studies, corneal staining is the most commonly reported complication of orthokeratology. Adverse events with orthokeratology have been reported in the literature to occur in low frequency 17,27–31 . The large majority of adverse events reported are minor and resolve without complications.…”
Section: Discussionmentioning
confidence: 99%
“…This result correlates well with the published literature. Bullimore et al 27 found that approximately only 3% of cases of microbial keratitis in orthokeratology wearers result in loss of best-corrected visual acuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the ever-growing global myopic population, 312 million people are under the age of 19 years [1]. Excessive axial elongation is associated with myopia, and this leads to structural changes in the posterior segment of the eye (including posterior staphyloma, myopic maculopathy, and high myopia-associated optic neuropathy) that may culminate in loss of best-corrected visual acuity in adulthood [2]. In addition, aging and the high utilization of touchscreen technology might increase the risk of eye diseases [3].…”
Section: Introductionmentioning
confidence: 99%